Is there a difference between the diversity of bees present in urban and rural environments? A study in Grecia, Costa Rica (Biocenosis, 2023)
Bees play a key role in the survival of many organisms, including humans. However, in recent years, their populations have experienced a drastic decline. The advancement of human civilization has led to the migration of many bees to urban environments where their adaptation is challenging, resulting in a decrease in their diversity. Therefore, it is important to understand the state of bee populations in both urban and rural environments to protect them. This study examines the diversity of diurnal bees found in urban and rural environments in Grecia, Alajuela, Costa Rica. Two collection methods (entomological net and trap plates) were applied in each location and environment during the period from September to November 2022, resulting in the collection of a total of 99 individuals that were taxonomically identified. Subsequently, by calculating the Simpson biodiversity index and the Jaccard similarity coefficient, it was concluded that rural environments exhibit greater diversity than urban ones. However, urban environments showed greater specific richness in terms of genera. It is worth noting that the yellow trap plates did not yield any positive results. Nevertheless, in future research, it would be necessary to analyze the variables that can significantly influence the collection of biodiversity data, such as climate, seasonality, sampling methods, and the composition of the environments under study.
Keywords: biodiversity; tropical bees; urbanization; conservation; Costa Rica